THE CORRELATION BETWEEN AFFECTIVE-COGNITIVE WRITING AND WRITING SKILLS - Nursyahida Suci Ramadhani; Sulastri Manurung; Aulia Putri (Universitas PGRI Sumatera Barat, 2025)
This study examined the relationship between students’ affective-cognitive writing strategies and their writing skills at the seventh-grade level of SMPN 21 Batam. The study employed a quantitative correlational design with a sample of 30 students selected through cluster random sampling to ensure representation of the population. Data were gathered using two primary instruments: the Affective-Cognitive Writing Strategies Questionnaire (ACWS) developed by Fisher (2010), which measures students’ affective and cognitive approaches to writing, and a descriptive writing test assessed using Brown’s (2007) analytic rubric. Assumption testing through the Shapiro-Wilk normality test and the linearity test confirmed that the data met the requirements for parametric analysis. Pearson’s Product Moment correlation showed that the use of affective cognitive writing strategies did not have a statistically significant relationship with students’ writing performance (r = -0.011, p = .954). These findings suggest that students’ writing performance was influenced more by their basic language proficiency and familiarity with the task than by their reported strategy use. Future studies with larger samples, multiple writing tasks, or qualitative data are recommended to provide deeper insights into how affective and cognitive factors contribute to students’ writing development. These results highlight the need for explicit instruction in both emotional regulation and cognitive strategy training in EFL writing classroom.